IMPROPER CONSTITUTION OF THE TRIBUNAL SEBAGAI DASAR PEMBATALAN PUTUSAN ICSID - Adinda Putri Prakasa, (2024)
The establishment of the International Centre for Settlement of Investment Disputes (ICSID) was driven by the objective of enabling an arbitration process characterized by complete autonomy, self-containment, and independence. One of the significant features of the ICSID system is the capacity to request the annulment of arbitral awards made under its auspices. The annulment process is governed by Article 52(1) of the ICSID Convention and is limited to the grounds set out there in without examining the merits or legal facts. Under Article 52(1)(a) of the ICSID Convention, either party may submit a written application seeking annulment on the grounds of the improper constitution of the tribunal. This ground is rarely invoked, and an award was only annulled for the first time in 2020. There is no consensus on the conditions under which this ground may be invoked. This research aims to discuss the applicable standard of the ICSID annulment grounds concerning the improper constitution of the Tribunal. A normative legal method focusing on the statute and case approaches is applied to achieve this objective. After reviewing previous legal cases, the annulment standard regarding the tribunal's improper constitution is quite uncertain within the ICSID framework. To improve the awards, scholars have proposed various proposals for reforming the ICSID annulment system.